Prognostic Value of Plasma Epstein–Barr Virus DNA for Local and Regionally Advanced Nasopharyngeal Carcinoma Treated With Cisplatin-Based Concurrent Chemoradiotherapy in Intensity-Modulated Radiotherapy Era. Issue 5 (February 2016) - Chen, Wen-Hui; Tang, Lin-Quan; Guo, Shan-Shan; Chen, Qiu-Yan; Zhang, Lu; Liu, Li-Ting; Qian, Chao-Nan; Guo, Xiang; Xie, Dan; Zeng, Mu-Sheng; Mai, Hai-Qiang
Abstract : Abstract: This study aimed to evaluate the prognostic value of plasma Epstein–Barr Virus DNA (EBV DNA) for local and regionally advanced nasopharyngeal carcinoma (NPC) patients treated with concurrent chemoradiotherapy in intensity-modulated radiotherapy (IMRT) era. In this observational study, 404 nonmetastatic local and regionally advanced NPC patients treated with IMRT and cisplatin-based concurrent chemotherapy were recruited. Blood samples were collected before treatment for examination of plasma EBV DNA levels. We evaluated the association of pretreatment plasma EBV DNA levels with progression-free survival rate (PFS), distant metastasis-free survival rate (DMFS), and overall survival rate (OS). Compared to patients with an EBV DNA level <4000 copies/mL, patients with an EBV DNA ≥4000 copies/mL had a lower rate of 3-year PFS (76%, 95% CI [68–84]) versus (93%, 95% CI [90–96], P < 0.001), DMFS (83%, 95% CI [76–89]) versus (97%, 95% CI [94–99], P < 0.001), and OS (85%, 95% CI [78–92]) versus (98%, 95% CI [95–100], P < 0.001). Multivariate analysis showed that pretreatment EBV DNA levels (HR = 3.324, 95% CI, 1.80–6.138, P < 0.001) and clinical stage (HR = 1.878, 95% CI, 1.036–3.404, P = 0.038) were the only independent factor associated with PFS, pretreatment EBV DNA level was the only significant factor to predict DMFS (HR = 6.292, 95% CI, 2.647–14.956, P < 0.001), and pretreatment EBV DNA levels (HR = 3.753, 95% CI, 1.701–8.284, P < 0.001) and clinical stage (HR = 2.577, 95% CI, 1.252–5.050, P = 0.010) were significantly associated with OS. In subgroup analysis, higher plasma EBV DNA levels still predicted a worse PFS, DMFS, and OS for the patients stage III or stage IVa-b, compared with those with low EBV DNA levels. Elevated plasma EBV DNA was still effective prognostic biomarker for local and regionally advanced NPC patients treated with IMRT and cisplatin-based concurrent chemotherapy. Future ramdomized clinical trials are needed to further evaluate whether plasma EBV DNA levels could be applied to guide concurrent chemotherapy regimen for local and regionally advanced NPC patients.